Equitable research partnerships : a global code of conduct to counter ethics dumping (2019)
In September 2015, after intensive public consultation, the international community went on record with a plan of action for people, planet and prosperity: the 2030 Agenda for Sustainable Development. All country representatives and all stakeholders expressed their determination to take the bold and transformative steps which are urgently needed to shift the world on to a sustainable and resilient path. As we embark on this collective journey, we pledge that no one will be left behind [emphasis added]. (UN 2015). To stimulate action, the heads of states and governments defined 17 sustainable development goals and 169 targets to be achieved by 2030. Successes in efforts to end extreme poverty, achieve food security and ensure healthy lives, as well as successes towards all other goals, depend not only on goal-oriented societal reforms and the mobilization of substantial financial and technical assistance, but also on significant technological, biomedical and other innovations. Ensuring the success of the Agenda 2030 requires massive research and development efforts as well new forms of research co-creation on a level playing field and with a universal professional ethos. Leaving no one behind does not “only” include reducing income and wealth inequalities, and affirmative action in support of better opportunities for selfdetermined living within and among countries. It also implies reaching those most at risk from poverty and its impacts. This again necessitates research focused on the needs of the poor in a way that does not infringe their human rights. Research and innovation can only be sustainably successful when based on societal trust. The precondition for societal trust and public acceptance is the perception that work is done with integrity and based on fundamental values shared by the global community. Trust depends not only on research work being compliant with laws and regulations, but also, more than ever, on its legitimacy. Such legitimacy can be achieved through inclusion and, importantly, the codesign of solutions with vulnerable populations. Leaving no one behind also means leaving no one behind throughout the research process, aiming for research with, not about, vulnerable populations.